Yahoo Answers is shutting down on 4 May 2021 (Eastern Time) and, as of 20 April 2021 (Eastern Time), the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Anonymous
Anonymous asked in Science & MathematicsMathematics · 2 months ago

# Why can't x-2/x-6 simplify to 1/3?

### 12 Answers

Relevance
• Because (x-2).(x-6) = 1/3 ONLY if x = 0

• x-2/x-6

x - (2/x) - 6

wherever did you get 1/3 ?

• 1/3 =

1/3 * (x - 2)/(x - 2) =

1(x - 2)/(3(x - 2)) =

(x - 2)/(3x - 6), not (x - 2)/(x - 6)

• Is x - (2/x) - 6 the same as 1/3? It depends on the value of x.

x - (2/x) - 6 = 1/3

Multiply through by 3x:

3x^2 - 6 - 18x = x

3x^2 - 18x - 6 - x = 0

3x^2 - 19x - 6 = 0

x = (-(-19) +/- sqrt((-19)^2 - 4(3)(-6))) / (2*3)

x = (19 +/- sqrt(361 + 72)) / 6

x = (19 +/- sqrt(433)) / 6

x =~ 6.6347753411141352717951502536839 or -0.30144200778080193846181692035056

So if x is one of those two values, then yes, you can simplify like that, but otherwise, no.

Or did you mean:

(x - 2) / (x - 6) = 1/3

Cross-multiply:

3(x - 2) = x - 6

3x - 6 = x - 6

3x - 6 - x + 6 = 0

2x = 0

x = 0/2

x = 0

So if x = 0, then yes, you can simplify like that, but otherwise, no.

• What do you think of the answers? You can sign in to give your opinion on the answer.
• x - 2 and x - 6 are not  common factors and cannot be equal to 1/3..

• Let x = 4

Hence

(4 - 2)/(4 - 6) =

2/2 = 1

This is just an example of using a non-zero number to show that (x -2)/(x -6) is no simply '1/3'.

• Assuming this is (x - 2) / (x - 6), x - 2 is one expression by itself and shares no common and cancellable factors with x - 6.  However, if x = 0, the entire rational expression will equal 1/3 ((0 - 2) / (0 - 6) = -2 / -6 = 1/3).

• Assuming you meant (x-2)/(x-6)

let's try one example to disprove it's 1/3:

If x = 2, then

(2-2)/(2-6) = 0, so you know for sure it's not 1/3

In fact, it's 1/3 for only where x=0, all other values it's some other value. • (x - 2) / (x - 6)

Because x isn't a factor so you can't just divide both sides by it to cancel them out.

That's like saying:

8 / 4

and you want to cancel out a 10 (x = 10 from your example).

That doesn't work.

• (x - 2)/(x - 6)

= x/(x - 6) - 2/(x - 6)

Root:

x = 2

Still have questions? Get answers by asking now.